Edward Said, Religion, and the Study of Islam: An Anglican view - Said, Yazid (Journal for the Academic Study of Religion, 2013)
This article examines the important, but controversial, analysis of Western readings of Islam by Edward Said in his Orientalism and other works. The thesis supports Said’s claim that a Western historical reading of Islam has a context and a framework of its own; but, it argues that Said falls into similar traps to those he critiques in the way he reasons away the significance of ‘religion’ in his investigation. This failure opens up for a different methodology of relating to Islamic religious texts and the study of Islam generally, using insights from Rowan Williams’s Why Study the Past?. While Said as well as certain Orientalists share scepticism about ‘religion’, this article points to the significance of theological and moral considerations in approaching religious texts.